Superwetting Electrospun PDMS/PMMA Membrane for PM2.5 Capture and Microdroplet Transfer - Lu, Nan (Langmuir : the ACS journal of surfaces and colloids, 2021)
Efficient acquiring and removal of a hazardous particulate matter (PM) have significant effects on human health. Here, we illustrate the fabrication of a superwetting electrospun polydimethylsiloxane/polymethyl methacrylate (PDMS/PMMA) membrane (EPPM) with multifunctional performance for PM2.5 capture and microdroplet transfer, where PMMA was added as a carrier polymer to the superhydrophobic PDMS, which has very low cohesive energy density. The obtained EPPM, which is composed of special bead-on-string fibers with a mean fiber diameter of 350 nm, shows a porous structure with an aperture of 7.87 μm (calculated by the bubble pressure method) and superb thermostability (up to 325 °C). The EPPM possesses an excellent PM2.5 purification efficiency of nearly up to 100% at a very low pressure drop (70 Pa, <0.07% of the atmospheric pressure) under the condition of high humidity (96 ± 3%), which is greatly advantageous over those hydrophilic filters frequently suffering the drawbacks of low efficiency or total invalidation in humid environments. In addition, benefitting from the superhydrophobic and strong adhesive properties of the membrane surface, the EPPM could complete the trace aqueous sample analysis such as "robotic hand" from superhydrophobic to hydrophilic surfaces without any contamination or loss and hold a high contact angle of 161.6° for water. Altogether, the EPPM may have technological advantages as a kind of novel fibrous filter in diverse environmental applications, including PM2.5 capture, separation, microdroplet transfer, and so on